Factors influencing Muslim credit card holders' impulse buying behaviour in Malaysia - Musadik, Siti Hajar Salwa Ahmad; Azmi, Ilhaamie Abdul Ghani (Malaysian Consumer and Family Economics Association, 2019)
Studies on impulse buying have been substantially conducted in developing countries by vast researchers. Nevertheless, such studies are in scarcity amidst Asian countries, particularly Malaysia. Besides, studies that have looked into the variables of materialism, sale promotion, money and time availability, and hedonic motivation are also rather sparsely carried out in the light of impulse buying behaviour. As such, this study examined the correlations between situational variables (sale promotion, money and time availability) and individual variable (materialism and hedonic motivation) with impulse buying behaviour among Muslim credit cardholders in Malaysia. In terms of instrument development, this study instrument consisted of 44 items adopted and adapted from prior studies. Questionnaires were distributed to 1,000 Muslim credit cardholders in Malaysia via purposive and snowball sampling techniques and only 635 were usable for final data analysis. The analysis was performed via Partial Least Square (PLS-SEM) analysis. The outcomes revealed that materialism, sale promotion, money and time availability, and hedonic motivation displayed significant positive correlations with impulse buying behaviour. © 2019, Malaysian Consumer and Family Economics Association. All rights reserved.